2004
DOI: 10.1016/j.jmmm.2003.11.265
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of ferromagnetic nanomagnets with vortex or single-domain configuration

Abstract: We study the dynamics of flat circular permalloy nanomagnets for 1.) magnetic vortex and 2.) single-domain configurations using micromagnetic simulation. Dynamical studies for isolated vortex structures show that both the vorticity and the polarity of the out-of-plane component can be switched fast (50-100 ps). Micromagnetic simulations of the switching process in thin cylindrical Permalloy(Py) nanoparticles with an initial stable singledomain state show nearly homogeneous single-domain behavior followed by ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…For example, domain wall motion can be described in terms of the dynamics of various types of magnetic topological solitons, i.e., transverse, vortex, and antivortex walls, via the sequential processes of the creation, propagation, and annihilation of them [3,4] in the Walker breakdown regime in magnetic nanostrips or simple motions of single solitons without any transformation of their internal structures [5]. Also, a single magnetic vortex in nanodots can be transformed into a new vortex with its core orientation opposite to the original core orientation via the serial processes of the creation and subsequent annihilation of vortexantivortex (VAV) pairs, with the help of vortex-core (VC) gyration motions [11][12][13][14][15][16][17].Furthermore, it has been reported that VC reversals can take place, possibly avoiding VC motions, under a specific condition of an intended immobile VC [18], by application of strong pulse fields perpendicular to the sample plane [19], or through a thermal excitation [20]. Regardless of the particular conditions and types of driving forces, the common reversal mechanism found thus far is the dynamic process of VAV-pair creation followed immediately by the annihilation of the newly created antivortex and the original vortex inside the nanoelements.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, domain wall motion can be described in terms of the dynamics of various types of magnetic topological solitons, i.e., transverse, vortex, and antivortex walls, via the sequential processes of the creation, propagation, and annihilation of them [3,4] in the Walker breakdown regime in magnetic nanostrips or simple motions of single solitons without any transformation of their internal structures [5]. Also, a single magnetic vortex in nanodots can be transformed into a new vortex with its core orientation opposite to the original core orientation via the serial processes of the creation and subsequent annihilation of vortexantivortex (VAV) pairs, with the help of vortex-core (VC) gyration motions [11][12][13][14][15][16][17].Furthermore, it has been reported that VC reversals can take place, possibly avoiding VC motions, under a specific condition of an intended immobile VC [18], by application of strong pulse fields perpendicular to the sample plane [19], or through a thermal excitation [20]. Regardless of the particular conditions and types of driving forces, the common reversal mechanism found thus far is the dynamic process of VAV-pair creation followed immediately by the annihilation of the newly created antivortex and the original vortex inside the nanoelements.…”
mentioning
confidence: 99%
“…Furthermore, it has been reported that VC reversals can take place, possibly avoiding VC motions, under a specific condition of an intended immobile VC [18], by application of strong pulse fields perpendicular to the sample plane [19], or through a thermal excitation [20]. Regardless of the particular conditions and types of driving forces, the common reversal mechanism found thus far is the dynamic process of VAV-pair creation followed immediately by the annihilation of the newly created antivortex and the original vortex inside the nanoelements.…”
mentioning
confidence: 99%